Thermodynamic analysis of a gas turbine cycle equipped with a non-ideal adiabatic model for a double acting Stirling engine. (1st September 2017) - Korlu, Mahmood; Pirkandi, Jamasb; Maroufi, Arman
Highlights: A gas turbine cycle equipped with a double acting Stirling engine is proposed. The hybrid cycle effects, efficiency and power outputs are investigated. The energy dissipation, the net enthalpy loss and wall heat leakage are considered. The hybrid cycle improves the efficiency from 23.6 to 38.8%. Abstract: The aim of this study is to investigate the thermodynamic performance of a gas turbine cycle equipped with a double acting Stirling engine. A portion of gas turbine exhaust gases are allocated to providing the heat required for the Stirling engine. Employing this hybrid cycle improves gas turbine performance and power generation. The double acting Stirling engine is used in this study and the non-ideal adiabatic model is used to numerical solution. The regenerator's net enthalpy loss, the regenerator's wall heat leakage, the energy dissipation caused by pressure drops in heat exchangers and regenerator are the losses that were taken into account for the Stirling engine. The hybrid cycle, gas turbine governing equations and Stirling engine analyses are carried out using the Matlab software. The pressure ratio of the compressor, the inlet temperature of turbine, the porosity, length and diameter of the regenerator were chosen as essential parameters in this article. Also the hybrid cycle effects, efficiency and power outputs are investigated. The results show that the hybrid gas turbine and Stirling engine improves the efficiency from 23.6 to 38.8%.